2016
DOI: 10.1177/2167479515623455
|View full text |Cite
|
Sign up to set email alerts
|

“I Was Able to Still Do My Job on the Field and Keep Playing”: An Investigation of Female and Male Athletes’ Experiences With (Not) Reporting Concussions

Abstract: This research applied muted group theory to investigate female and male athletes’ experiences with not reporting concussions sustained during athletic competition. Using snowball-sampling techniques, a total of 365 women and 247 men completed an online open-ended questionnaire about their reasons for not reporting a concussion. Results indicated that male athletes were more likely to continue to play through and not report a concussion than female athletes. Participants also indicated that they did not report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 35 publications
3
52
0
Order By: Relevance
“…Although many sport-related concussions occur annually (Langlois et al, 2006), researchers have found that athletes are hesitant to report concussions due to concerns about being perceived as weak, not being a good teammate, not being believed, or due to pressure from coaches, teammates, fans, or parents (Cranmer & LaBelle, 2018;Kroshus et al, 2015a;Sanderson, et al, 2017;Weinberg et al, 2013). Coupling these self-perceptions with the physiological, emotional, social, and mental effects of concussions (Bloom, Horton, McCrory, & Johnston, 2004;McCrory et al, 2017), athletes may perceive concussions as a health stigma, or, "an individual's perception that her or his health condition represents a mark of discredit" (Wright & Rains, 2013, p. 310).…”
Section: Athletes Concussions and Health Stigmasmentioning
confidence: 99%
See 4 more Smart Citations
“…Although many sport-related concussions occur annually (Langlois et al, 2006), researchers have found that athletes are hesitant to report concussions due to concerns about being perceived as weak, not being a good teammate, not being believed, or due to pressure from coaches, teammates, fans, or parents (Cranmer & LaBelle, 2018;Kroshus et al, 2015a;Sanderson, et al, 2017;Weinberg et al, 2013). Coupling these self-perceptions with the physiological, emotional, social, and mental effects of concussions (Bloom, Horton, McCrory, & Johnston, 2004;McCrory et al, 2017), athletes may perceive concussions as a health stigma, or, "an individual's perception that her or his health condition represents a mark of discredit" (Wright & Rains, 2013, p. 310).…”
Section: Athletes Concussions and Health Stigmasmentioning
confidence: 99%
“…Accordingly, online forums provide unique spaces for athletes to share their concussion recovery experiences in ways that are personally meaningful (Varga & Paulus, 2014) and to convey information they may not disclose offline. These outcomes are particularly salient given the stigmas associated with sport cultural norms surrounding athletes and toughness (Sanderson et al, 2017). Thus, online forums enable athletes, through narratives, to share their experiences with social support as they describe living with their concussion injury.…”
Section: Social Support and Online Support Forumsmentioning
confidence: 99%
See 3 more Smart Citations